THE RELATIONSHIP BETWEEN IRON TABLET CONSUMPTION AND ANEMIA IN PREGNANT WOMEN IN SINTANG REGENCY, WEST KALIMANTAN - Elvi Juliansyah; Yunida Haryanti; Lea Masan; Ria Damayanti (PT. Jurnal Center Indonesia Publisher, 2025)
Anemia is a medical condition where the number of red blood cells or hemoglobin levels in the blood is below normal, which is a protein in red blood cells that functions to carry oxygen from the lungs to the entire body. The prevalence of anemia in pregnant women in Sintang Regency showed that in 2017 there were 116 cases, in 2018 there were 121 cases, and in 2019 there were 164 cases. This research method uses a quantitative analytical approach with a cross-sectional design in Sintang Regency. The population is all pregnant women registered as many as 369 respondents within the scope of the Health Center services in Sintang Regency during the data collection period. The simple random sampling technique was used to select respondents, with a sample size of 192 pregnant women after calculating the population size. The results showed that there was a relationship between knowledge with a p value = 0.000 and OR = 6.900, parity with a p value = 0.000 and OR = 5.040, consumption of iron tablets with a p value = 0.000 and OR = 5.271 with the incidence of anemia in pregnant women in Sintang Regency. The most dominant multivariate test result is knowledge with OR = 7.25 followed by consumption of iron tablets with OR = 4.61 and parity with OR = 4.26. The conclusion related to the incidence of anemia in pregnant women is knowledge, parity, and consuming iron tablets and the most dominant is knowledge and followed by consumption of iron tablets, and parity. It is recommended that pregnant women can improve their knowledge, multi and grandi para pregnant women to comply with consuming iron tablets routinely.